2016
DOI: 10.1002/slct.201600278
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Hybrid Carbon via Graphitization of Polystyrene–co‐Divinylbenzene: Morphology, Structure and Adsorption Properties

Abstract: Multilayer graphitic nanosheets/nanoshells have been obtained via pyrolysis at 850 8C of poly(4-ethylstyrene-co-divinylbenzene) (PS-co-DVB) by inflowing Fe(II)-acetylacetonate (Fe(ACAC) 2 ) into the pores of the polymer. Iron-free PS-co-DVB was also pyrolyzed at the same temperature, thus highlighting the effective role of the catalyst in promoting the graphitization at relatively moderate temperatures. It will be shown that under longer annealing times at 850 8C in presence of Fe 3 C and a-Fe the carbon precu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…The upshift of the 2D peak suggested that the carbon structures of the nanofibers became more ordered at higher carbonization temperatures. Moreover, it is reported that 2D peak is symmetric in turbostratic graphite because of the absence of the AB stacking order which induces the doublet structure (asymmetry) of the 2D peak (Cesano et al, 2016). Here, symmetric 2D peaks were observed for C800 and C1000 while the asymmetry of the 2D peak became more and more obvious in C1200 and C1400, again indicating more ordered carbon structures in C1200 and C1400.…”
Section: Resultsmentioning
confidence: 75%
“…The upshift of the 2D peak suggested that the carbon structures of the nanofibers became more ordered at higher carbonization temperatures. Moreover, it is reported that 2D peak is symmetric in turbostratic graphite because of the absence of the AB stacking order which induces the doublet structure (asymmetry) of the 2D peak (Cesano et al, 2016). Here, symmetric 2D peaks were observed for C800 and C1000 while the asymmetry of the 2D peak became more and more obvious in C1200 and C1400, again indicating more ordered carbon structures in C1200 and C1400.…”
Section: Resultsmentioning
confidence: 75%
“…All these minor features reveal the role played by the Fe catalyst in assembling carbon domains (from amorphous to the more crystalline) via the decomposition of C 2 H 4 . Ethylene is known in catalysis not only for the catalytic polymerization/oligomerization [42], but also for the formation of carbon nanostructures, including single-walled carbon nanotubes (SWCNTs) [43], multi-walled carbon nanotubes (MWCNTs) [44], graphene [45], and curved graphitic domains [46]. To gain more insight into the structure and morphology of samples after being contacted with C 2 H 4 at 750 • C, TEM images were acquired.…”
Section: Morphology Structure and Chemical Composition Of Fe-titanatmentioning
confidence: 99%
“…Carbon–based systems of different dimensionality, such as single/multiwalled carbon nanotubes, graphene-like, activated carbons, and carbon-based aerogels have attracted an increasing attention in the past and at the time of writing this paper. Recent works have shown that all these nanocarbons have distinctive properties, including electrical conductivity, chemical inertness, sorption, sensing, and biosensing (Cravotto et al, 2011 ; Cesano et al, 2012b , 2016 ; Holzinger et al, 2014 ; Badhulika et al, 2015 ; Li et al, 2015 ; Niu et al, 2015 ; Kotal et al, 2016 ). In the majority of cases, such properties can be better exhibited if nanocarbons are confined in another phase (i.e., polymers) (Wu et al, 2012 ; Cesano et al, 2013 ; Cravanzola et al, 2013 ; Niu et al, 2015 ), or are combined with other systems to form heterostructures (Wang et al, 2010 ; Ong, 2017 ; Rho et al, 2017 ), hybrids (Badhulika et al, 2015 ; Wang et al, 2016 ), composites (Bai and Shen, 2012 ), or simply when they are decorating the surface of inorganic solids (Wu et al, 2012 ; Cravanzola et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%